Increased Peripheral Interleukin 10 Relate to White Matter Integrity in Schizophrenia - Fu, Gui; Zhang, Wenjing; Dai, Jing; Liu, Jieke; Li, Fei; Wu, Dongsheng; Xiao, Yuan; Shah, Chandan; Sweeney, John A.; Wu, Min; Lui, Su (Frontiers in Neuroscience, 2019)
Background: Schizophrenia is characterized by the disruption of microstructural white matter (WM) integrity, while the pathogenesis remains unclear. Inflammation has been associated with the WM pathology in schizophrenia. Interleukin 10 (IL-10) has been proven to be related to schizophrenia in both animal and human models. The aim of this study was to explore whether peripheral IL-10 was associated with microstructural WM integrity in schizophrenia. Methods: A total of 47 patients with schizophrenia (SZ) and 49 healthy controls (HC) underwent diffusion tensor imaging and venous blood sampling. Tract-based spatial statistics was conducted to explore the differences in fractional anisotropy (FA), radial diffusivity (RD), mean diffusivity (MD), and axial diffusivity (AD) between patients and controls. A quantitative chemiluminescence assay was performed to measure peripheral IL-10 levels. General linear regression analysis using a stepwise method was applied to examine the relationship between peripheral IL-10 and diffusion measures. Results: Compared with the HC, peripheral IL-10 levels were higher and a significant reduction of FA and AD, and increase of RD and MD were observed in SZ (corrected p < 0.05). A regression analysis revealed that peripheral IL-10 was negatively correlated with FA in the right posterior thalamic radiation and left inferior fronto-occipital fasciculus, in SZ (β = -0.51, p = 0.01; β = -0.47, p = 0.02, respectively) but not in HC (β = -0.01, p = 0.95; β = -0.003, p = 0.98, respectively), and the differences in regression curves were significant (z = 2.50, p = 0.01; z = 2.37, p = 0.02, respectively). IL-10 was negatively connected with MD in the right parietal arcuate fasciculus (β = -0.40, p = 0.048) and body of the corpus callosum (β = -0.43, p = 0.03) in SZ, while not in HC. The magnitude of correlation in the patient and control group was different (z = 2.48, p = 0.01 and z = 2.61, p < 0.01, respectively). In addition, IL-10 was positively correlated with RD in the right parietal arcuate fasciculus in patients (β = 0.45, p = 0.04) but not in HC (β = 0.26, p = 0.94), but the correlation coefficients were not significant (z = 0.98, p = 0.32). Conclusion: Our findings demonstrated that elevated peripheral IL-10 levels were associated with the disruption of microstructural WM integrity in schizophrenia, supporting the notion that inflammation plays a regulatory role in the pathology of microstructural WM and is associated with schizophrenia.